2019
DOI: 10.1021/acsinfecdis.9b00207
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and PET Bioimaging of 76Br-Bedaquiline in a Murine Model of Tuberculosis

Abstract: Bedaquiline is a promising drug against tuberculosis (TB), but limited data are available on its intralesional pharmacokinetics. Moreover, current techniques rely on invasive tissue resection, which is difficult in humans and generally limited even in animals. In this study, we developed a novel radiosynthesis for 76 Br-bedaquiline and performed noninvasive, longitudinal whole-body positron emission tomography (PET) in live, Mycobacterium tuberculosis-infected mice over 48 h. After the intravenous injection, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Several key and newer TB drugs, including rifampin, pyrazinamide, isoniazid, linezolid, and bedaquiline, have been radiolabeled to provide noninvasive PK data with PET imaging ( Table 3 and refs. 13 and 74 77 ). PET imaging can directly visualize multiple compartments simultaneously and monitor changes over time, thereby reducing sampling bias.…”
Section: Antimicrobial Biodistributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several key and newer TB drugs, including rifampin, pyrazinamide, isoniazid, linezolid, and bedaquiline, have been radiolabeled to provide noninvasive PK data with PET imaging ( Table 3 and refs. 13 and 74 77 ). PET imaging can directly visualize multiple compartments simultaneously and monitor changes over time, thereby reducing sampling bias.…”
Section: Antimicrobial Biodistributionmentioning
confidence: 99%
“…Ordonez et al demonstrated lower penetration of 11 C-rifampin in cavitary walls, which are associated with a high bacterial burden, compared with other types of TB lesions as well as independent temporal evolution of different TB lesions in the same patient during treatment ( 13 ). Ex vivo autoradiography can also be used with other staining techniques, such as immunofluorescence, in animals after PET to provide high-resolution intralesional biodistribution similar to MALDI-MSI ( 74 ). Multimodality imaging can also provide valuable information on the interaction of the host response and drug penetration.…”
Section: Antimicrobial Biodistributionmentioning
confidence: 99%
“…Since the most highly ranked determinants of microbial outcomes in patients with TB are drug concentrations, between-patient pharmacokinetic variability, Mtb MIC variability, PK/PD exposures, and lung intralesional penetration, we integrated each of these factors in Monte Carlo experiments to identify clinical doses that would achieve or exceed the HFS-TB exposures shown in Figure 2, using steps outlined in online methods. 2,4,7,10,22,32,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Figure 3 and supplementary data text show that the in-silico dosing achieved the same serum pharmacokinetic parameters and concentrations observed in actual patients. Figure 4 shows that the bedaquiline, delamanid, OPC, pretomanid, and sutezolid exposures achieved in our HFS-TB experiments could easily be achieved in lung TB cavities at doses tolerated by patients in the clinic.…”
Section: Hfs-tb Concentrations Achieved In Patient Lesions and Modele...mentioning
confidence: 99%
“…49 (D) 76 Br-Bedaquiline is obtained by coppermediated nucleophilic radiobromination of the boronic pinacol ester precursor. 57 Journal of Medicinal Chemistry…”
Section: -18mentioning
confidence: 99%